A Water-Based Sequential Preparatory Approach vs. Conventional Aquatic Training in Stroke Patients: A Randomized Controlled Trial With a 1-Month Follow-Up - Temperoni, Giulia; Curcio, Andrea; Iosa, Marco; Mangiarotti, Marco Antonio; Morelli, Daniela; De Angelis, Sara; Vergano, Serena; Tramontano, Marco (Frontiers in Neurology, 2020)
Background: Many studies hypothesize that people who have suffered stroke could benefit from water-based exercises to improve their strength and ability to perform the activities of daily living. Objective: The study aim was to compare the effects of a water-based sequential preparatory approach (SPA) and conventional aquatic therapy in improving motor functions and quality of life in patients with chronic stroke. Methods:Thirty-three chronic stroke outpatients diagnosed with hemiplegia were recruited and randomly assigned to the experimental or the control group. Subjects in the experimental group underwent a trial water-based SPA balance training and patients in the control group were given traditional water balance training. Both groups of participants underwent 45 min of therapy twice a week for 4 weeks. All patients were evaluated before treatment (T0), after 4 weeks of training (T1) and 4 weeks after the end of training (T2) using the Berg Balance Scale (BBS), the Modified Barthel Index (BIM), the Tinetti Balance and Gait Scale (TBG), the Stroke Specific Quality Of Life Scale (SS-QOL) and the Modified Ashworth scale (MAS). Results:After the training, statistically significant differences (p<0.05) were found between the groups in their score averages on the BBS (p=0.01) and the SSQOL scale (p=0.03). Furthermore, the SPAg showed a significantly greater percentage of improvement on the BBS (p=0.02) and the SSQOL (p=0.03). Both groups obtained a significantly improved MAS score (p<0.01). Conclusion:Results indicate that water training based on a sequential preparatory approach is more effective than traditional aquatic training for balance rehabilitation of chronic post-stroke patients.